2009
DOI: 10.1111/j.1530-0277.2009.00911.x
|View full text |Cite
|
Sign up to set email alerts
|

β‐Endorphin Neuronal Cell Transplant Reduces Corticotropin Releasing Hormone Hyperresponse to Lipopolysaccharide and Eliminates Natural Killer Cell Functional Deficiencies in Fetal Alcohol Exposed Rats

Abstract: Background Natural killer (NK) cell dysfunction is associated with hyperresponse of corticotropin releasing hormone (CRH) to immune challenge and with a loss of β-endorphin (BEP) neurons in fetal alcohol exposed animals. Recently, we established a method to differentiate neural stem cells into BEP neurons using cyclic adenosine monophosphate (cAMP)-elevating agents in cultures. Hence, we determined whether in vitro differentiated BEP neurons could be used for reversing the compromised stress response and immun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
62
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 43 publications
(64 citation statements)
references
References 28 publications
2
62
0
Order By: Relevance
“…In the current study, we investigated whether β-EP neuronal transplantation could attenuate the elevated anxiety-like behavior and the corticosterone response to acute restraint stress in fetal alcohol exposed rats. Previously, we have shown that β-EP neuronal transplantation into the PVN of the hypothalamus reduces the response of hypothalamic CRH neurons to an immune stressor and modulates the peripheral stress response during and following a stressor (Boyadjieva et al, 2009; Sarkar and Zhang, 2013). …”
Section: Introductionmentioning
confidence: 99%
“…In the current study, we investigated whether β-EP neuronal transplantation could attenuate the elevated anxiety-like behavior and the corticosterone response to acute restraint stress in fetal alcohol exposed rats. Previously, we have shown that β-EP neuronal transplantation into the PVN of the hypothalamus reduces the response of hypothalamic CRH neurons to an immune stressor and modulates the peripheral stress response during and following a stressor (Boyadjieva et al, 2009; Sarkar and Zhang, 2013). …”
Section: Introductionmentioning
confidence: 99%
“…Alteration in feedback inhibition of the HPA axis by glucocorticoids (GCs) or β-endorphin (β-EP) at the level of the PVN (Hellemans et al, 2010; Boyadjieva et al, 2009)…”
Section: Figmentioning
confidence: 99%
“…These effects of ethanol on the Pomc gene were associated with some functional and behavioral abnormalities in FASD patients [139,140,141] (Fig. 1).…”
mentioning
confidence: 93%